The Effect of Influencer Authenticity on Purchase Intention Mediated by Trust Transfer in Increasing Ventela Brand Consumers - Farizha Dwi Kartika; Siska Ernawati Fatimah (Interdisciplinary Social Studies, 2026)
The development of digital marketing encourages the increasing use of influencers as a promotional strategy, especially for local products marketed through online marketplaces. However, the effectiveness of influencer marketing is largely determined by the level of authenticity of influencers in building consumer trust. This study aims to analyze the influence of influencer authenticity on purchase intention with trust transfer as a mediating variable in consumers of Ventela shoe products in the Cirebon City marketplace. The study used a quantitative approach with a survey method of 200 respondents who had an interest and experience of being exposed to Ventela's promotion by influencers. Data were collected through an online questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study show that influencer authenticity has a positive and significant effect on purchase intention. In addition, influencer authenticity also has a significant effect on trust transfer, and trust transfer has a significant effect on purchase intention. The results of the mediation test showed that trust transfer partially mediated the relationship between influencer authenticity and purchase intention. These findings indicate that influencer authenticity not only influences purchase intent directly, but also through the mechanism of transferring trust from influencers to brands. This research provides theoretical and practical contributions in the development of trust-based influencer marketing strategies to increase the competitiveness of local products in the digital marketplace.